If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4x = -6x Solving 8 + -4x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 8 + -4x + 6x = -6x + 6x Combine like terms: -4x + 6x = 2x 8 + 2x = -6x + 6x Combine like terms: -6x + 6x = 0 8 + 2x = 0 Add '-8' to each side of the equation. 8 + -8 + 2x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 0 + -8 2x = 0 + -8 Combine like terms: 0 + -8 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 1/3n=2/3 | | 1.25+3.69/0.3=47.9 | | 5n+12=27 | | 20+x=-5 | | 4x^2-9x-60=0 | | 7=x-.2 | | -30+x=-17 | | (1+y)(5y-8)=0 | | 5x+44=9x+2 | | 194-5x=40x+19 | | x+.3=5 | | 13-8x=70-29x | | 5/6s+3/4=11/12 | | t/6+3=8 | | 9x+1=26 | | 37+12m=85 | | -44=-3m-2 | | 3x+2g= | | -5(x+4)=7(x-2) | | 0.75x+.05(14-x)=.10(91) | | (v+1)(v-6)= | | 12x^2/36x | | -40=8-6m | | 7x^1/2=-21x | | -6x-33=-14x+47 | | 6x-33=14x+47 | | 24=5x+3-2x | | 6x+33=-14x+47 | | 6x+33=14x+47 | | 9x+5y+7y-5x+4z-6y= | | 8/56 | | 18x+8=12x+15 |